KEWENANGAN PEMERINTAH DAERAH KOTA BOGOR DALAM PENGENDALIAN PEREDARAN MINUMAN BERALKOHOL: The Authority of Bogor City Government in Controlling the Distribution of Alcoholoc Beverages - Siti Nur Rizqiah; Ninuk Wijiningsih (AMICUS CURIAE, 2025)
The Bogor City Government has the authority to control the circulation of alcoholic drinks through Bogor Mayor Regulation Number 121 of 2022. This regulation aims to regulate the distribution, licensing, supervision and control of alcoholic drinks in order to maintain public order and protect the public from the negative impacts of alcohol consumption. In its implementation, supervision is carried out by the Bogor City Civil Service Police Unit and the Industry and Trade Service. In its implementation, this policy still faces various obstacles, including the practice of bribery in licensing, misuse of distribution permits, and the continued distribution of illegal alcoholic beverages. The identification problem with this research is that law enforcement carried out through raids is often not effective due to information leaks which enable business actors to avoid legal action. In addition, new challenges arise with the development of online commerce which makes it difficult to monitor the distribution of illegal alcoholic beverages. This type of research is normative juridical, descriptive in nature, using secondary data as main data and primary data as supporting data, as well as drawing deductive conclusions to analyze the effectiveness of policies to control the circulation of alcoholic beverages in Bogor City. The research results and conclusion show that although this regulation has been made comprehensively, its implementation still requires improvements in the aspects of supervision, inter-agency coordination, and education to the public to ensure the effectiveness of the policy in the long term.